Mobile technology in civil engineering programs (Gaceta Técnica, 2016)
Today it is evident the use of technologies in all activities people do, becoming an inevitable phenomena socially, at work and educational. In terms of work, one can see how companies are using technologies as tools to do many activities inside and outside of it like the use of mobile dispositive enhancing new managerial models like the company mobility. The new organizational models are making civil engineering programs to point out the skills students should have during a professional training in order to fulfill in an organization with a company mobility model. It is also important to consider the competences of students that have been conceived by the effect of technological developments, where you can see Students that use and receive information in a very fast way, prefer and plan networking, apply and multitask parallel processes, and are able to handle any devices, in special Mobile, among other attributes. These characteristics activate in students the BYOD Principle, which strengthen their technological skills within the university context, inducing students in civil engineering, to learn the culture of bringing their own device to the learning environment before being transferred to the employment context, important attribute Faced with the adoption of enterprise mobility model.
Keywords: mobile devices; enterprise mobility; civil engineering